Arquitetura do Ferro do Rio de Janeiro - Santos Lima Carlos, Dr. Arq. Claudio Antonio (Universidad Nacional del Litoral, 2013)
The text proposes a reflection regarding the prefab architecture made of iron from its emergence in 19th century Europe to present days, by theoretical reference to material available in specialized bibliography related to the subject that highlights mobility and temporariness as its main innovations, among others. It assesses critically the destination of the legacy of the expansion of this construction method in Brazil, especially in the city of Rio de Janeiro, where the apropriations and destinations of three significant sets are originally located: the Market Hall of Rio de Janeiro (Mercado Municipal do Rio de Janeiro) located at the November 15th Square - City Center (Praça XV de Novembro - Centro), and considered the major specimen of this category in Latin America; the shed known as Trajano Shops, located in the Engenho Novo area, which was part of the Paris  World Exposition (Exposição Universal de Paris), 1889; and the group of sheds of the Federal Rail Network’s shops in the same area. These specimens embody a turbulent context of negligence, legal protection and illegal demolition, displaying a situation of ignorance by the public administration concerning the importance of this arquitecture as clear exhibits of the 19th century emerging modernity.